2016
DOI: 10.1038/hdy.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of the relationships between Ne, Nb and Nc towards defining conservation thresholds in Atlantic salmon (Salmo salar)

Abstract: Effective population size over a generation (Ne) or over a reproductive cycle (Nb) and the adult census size (Nc) are important parameters in both conservation and evolutionary biology. Ne provides information regarding the rate of loss of genetic diversity and can be tracked back in time to infer demographic history of populations, whereas Nb may often be more easily quantified than Nc for short-term abundance monitoring. In this study, we propose (1) an empirical context to Waples et al. (2014) who introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 79 publications
3
62
1
Order By: Relevance
“…There was no significant correlation between N b and N c across 10 years in the River Nivelle. Indeed, N b and N c did not co‐vary across years leading to high inter‐annual variation of N b : N c as previously reported for the species (Palstra et al, ; Ferchaud et al, ; Perrier et al, ). This typical variation in N b : N c in combination with lack of correlation between N b and N c may indicate that variance in reproductive success could be an important factor in N b variation in this population, in addition to the number of individuals that effectively reproduced (Luikart et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant correlation between N b and N c across 10 years in the River Nivelle. Indeed, N b and N c did not co‐vary across years leading to high inter‐annual variation of N b : N c as previously reported for the species (Palstra et al, ; Ferchaud et al, ; Perrier et al, ). This typical variation in N b : N c in combination with lack of correlation between N b and N c may indicate that variance in reproductive success could be an important factor in N b variation in this population, in addition to the number of individuals that effectively reproduced (Luikart et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, genetic monitoring of effective population size has been recognized as a complementary resource for conservation planning (Dodson et al, ). Routine implementation in population management, however, has not followed, probably due to the continuous development of refined methods over the past decade (Wang et al, ) and the limited number of studies showcasing practical applications in the context of population management (but see Ozerov et al, ; Whiteley et al, ; Ferchaud et al, ; Perrier et al, for recent examples). A second objective of this study is to bridge the gap between academia and resource management practice.…”
Section: Introductionmentioning
confidence: 99%
“…Heggenes et al., ; Østergaard et al., ), whereas others have failed to detect it (e.g. Ferchaud et al., ; Palstra & Ruzzante, ; Vähä et al., ). Some mutually non‐exclusive explanations may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Most taxa still have little N b /N c data emerging, but sufficient data have become recently available in three fishes from the Salmoninae subfamily (Chinook salmon, Atlantic salmon and brook trout); these species form the basis of our quantitative analysis of N b /N c relationships. The studies examining these species have largely found positive relationships between N b and N c (e.g., Bernos & Fraser, ; Ferchaud et al., ; Perrier et al., ; Van Doornik, Waples, Baird, Moran, & Berntson, ; etc. ); we collated data across studies to produce models for converting N b to N c (and vice versa) in each species.…”
Section: Introductionmentioning
confidence: 99%